Response of spinach and Spodoptera exigua to organic and mineral fertilization - Perzabal-Ramos, Maythed; Sandoval-Castro, Engelberto; Díaz-Ruíz, Ramón; Huerta-de la Peña, Arturo; Figueroa-Brito, Rodolfo; Bahena-Juárez, Fernando (Revista Mexicana de Ciencias Agrícolas, 2018)
Farmers face serious phytosanitary risks and phytosanitary problems, it is generally assumed that the increase of nitrogen (N) in the plant increases the populations of pathogens. The study was carried out in the greenhouse to know the effects of the spinach (Spinacia oleracea L.) variety of Python F1, as well as the response that exists in the oviposition of females and the damage caused by larvae of Spodoptera exigua. It was fertilized with mineral fertilizer based on Steiner nutrient solution (100%, 50%) and with biofertilizers of rabbit leachate (3%) and cachaça compost (1:1 v/v). By means of the ImageJ® program the damaged area of the leaves were calculated and for the leaf area dynamics the PROC NLIN using logistic models. A statistical analysis was performed for agronomic variables, oviposition and spinach damage using Tukey test (p≤ 0.05). The results showed differences in the fresh weight of the plant (PSP) and the root (PFR), the largest leaf area was the combination treatment of cachaza compost and complete Steiner solution SN (100%), no differences were observed in the treatments at 45 and 60 days after the emergency. Regarding Spodoptera exigua, differences were found in the number of egg masses at 24 h (NMHP24), weight of the larvae (PL), number of damaged leaves (NHD) and area of the damaged leaf (AHD). The rabbit leachate can be an alternative as a biofertilizer for an organic production in spinach.